The relationship between psychological adjustment and academic engagement among undergraduate student at International Islamic University Malaysia - Goudih, Zohra (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Academic engagement and psychological adjustment are important factors that contribute to student's success. This study aims to investigate the relationship between these two variables and the predictors that can affect them in the context of undergraduate students at International Islamic University in Malaysia. To find out if there are any differences in them attributable to gender, age, nationality, year of study and faculty, and determine the nature of the relationship between psychological adjustment and academic engagement. Data were collected from a sample of 426 undergraduate students at IIUM using two main instruments: the student Adjustment to college Questionnaire (SACQ) and the National Survey of student engagement (NSSE). Descriptive statistics were used for determining the degrees of academic engagement and psychological adjustment, ANOVA and T-test to determine differences in student adjustment and engagement based on demographic variables, while correlation analysis was used to investigate the relationship between the two variables. Result showed that there was a moderate positive relationship between academic engagement and psychological adjustment among IIUM undergraduate. ANOV A result showed significant differences in (Personal-emotion adjustment) between local student and international students; in (academic adjustment) between students from Kuliyyah of IRKH and ENGIN; in (peer to peer) between males and females; and in (student engagement with university) between local international students. The overall finings indicated that there was a relatively low level of academic engagement, the institution to conduct more programs to increase student engagement among undergraduate students.